VISUALISASI NABI SAW DALAM FILM PERPEKTIF HUKUM ISLAM - Atik Fikri Ilyas; Dini Indah Wulandari (Program Studi Hukum Keluarga Islam, 2017)
This paper describes the law of visualization of the Prophet Muhammad in the film. Progress of the era demands the contextualization of Islamic teachings, including educational entertainment. Some parties the presence of films that take the theme of Islam becomes a necessity. Including the theme of the film about the history of the Prophets, up to the Prophet Muhammad SAW. Because it appears the pros and cons of visualization of the Prophet SAW in the film. This paper highlights the problematic. It is hoped that this paper will become a common thread for the visualization of the Prophet (s) in the film can be seen comprehensively from the view of Islamic law. For the next can be a consideration to take an attitude over the visualization of the Prophet in the film.